Reflections on the possible application of Rome I Regulation to obligations related to crypto-assets - Mariański, Michał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
Regulation No. 2023/1114 of the European Parliament and Council of 31 May 2023 on cryptoasset markets is a crucial component of financial market regulation that has significantly contributed to increasing the legal security of its participants. This study does not aim to analyse the basic rules of crypto-asset trading or make an assessment of their legal status but rather seeks to determine how the law applicable to obligations related to crypto-assets could be determined. Linking a given transaction to more than one legal area is one of the essential features of modern global financial markets. Given the above, this paper analyses possible subsidiary application of the Regulation No. 593/2008 on the law applicable to contractual obligations (Rome I to cryptoassets). The primary research method employed is the dogmatic-legal method, supplemented by the theoretical-legal method. The most important goals of these research methods are to identify the scope of validity of given norms, analyse their practical application, and draw conclusions. Both methods were used to determine whether the scope of the Rome I regulations allows the application of its provisions to obligations related to crypto-assets. Therefore, this article seeks to address whether the rules related to contractual obligations can also be applied to crypto-assets. The arguments presented in this work do not exclude such a possibility. However, the author notes that the level of regulation of financial markets in terms of conflicts of laws cannot be considered sufficient and completed.